Are There Differences in Student Competency based on Gender, Semester Level and Age in Applying ICT-based Guidance and Counseling Services? - Hartini Hartini; Edi Wahyudi M (STAI Hubbulwathan Duri, 2023)
This study aimed to assess students' proficiency in utilising Information and Communication Technology-based advice and counselling services. The analysis was conducted considering factors such as gender, semester level, and age range. The research method employs a quantitative approach by utilising a questionnaire instrument consisting of a total of 33 items. The study participants consisted of a saturated sample of 32 postgraduate students, meaning that the entire population was included in the research. The data were analysed via a quantitative descriptive methodology and t-test. The results from the study showed that the competency score of male students was higher than that of females, but the results of the different tests obtained a score of 1.092 with a sign of 0.291 ( 0.05), which explained that the hypothesis was accepted, namely the two average competencies of male and female students. There is no difference. While the competence of second-semester students obtained a lower competency score compared to the fourth semester with the acquisition of a t-count value of 2.082 with sign 0.046 (0.050), it can be concluded that there are differences in the competence of students II and IV in applying Guidance and counseling (BK) services through ICT-based media. Generation Y student competencies get higher scores in height compared to Generation X with the acquisition of t count 2.243 with sig 0.32 (0.050), which explains that there are differences in the competence of students of Generation X and Y so that students in the age range of 22-41 years more able to apply the media of ICT-based guidance and counseling services compared to students aged 42-62 years.